Produção e caracterização estrutural, morfológica e térmica de filmes biodegradáveis utilizando amido de caroço de abacate (Persea americana Mill) e bagaço de mandioca (Manihot esculenta Crantz) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
The development of biodegradable packaging has been studied in order to replace synthetic polymers in an attempt to reduce the environmental impact of this material. Starch and vegetable fibers, appears as a potential option for the production of alternative materials for this purpose, especially in food applications. This project aims to obtain and characterize raw materials and biodegradable films produced from starch extracted from avocado and cassava bagasse. Initially, three different extraction forms were tested: aqueous, alkaline and acidic, and from that, different film formulations were formed, among them starch and fiber mixtures, only fiber and starch only. Both microscopic analysis and x-ray diffraction showed that the different types of starch extractions did not show any structural difference, nor did their crystallinity pattern change, however, the centesimal analysis confirms that the chemical extractions helped to purify the starch granules, compared to aqueous extraction. The amylose content in the avocado did not present a significant difference in relation to the extraction method. Values of 33.6, 32.8 and 32.1% of amylose were obtained in the analysis for the aqueous, alkaline and acid extracted starches, respectively. For the films formed, although there was no highlight among the samples containing fibers, the values of all the analyzes for the mixtures formed were inferior to the films formed with starch alone. Among these, the acid-extracted sample was that presented the best results, presenting values of 31.33 ± 0.73% of moisture, 24.63 ± 2.66 g / 100g of solubility, mechanical resistance of 3.12 ± 0.35 N / mm2. About the analysis of atomic force microscopy (AFM), the sample containing aqueous extracted in its composition, was the one that presented a lower value of roughness, 25.8 nm, whereas when adding cassava bagasse this value was changed to 289.8 nm. These results could also be observed in microscopic images formed in three dimensions. In general, seed starch avocado is applicable to the formation of biodegradable films, however, the proportion of fibers added, their size and botanical origin should be checked for an improvement in the properties of the material.
Keywords: amido termoplástico; casting; polímero natural; resíduos agroindustriais; thermoplastic starch; casting; natural polymer; agroindustrial waste; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS